2011
DOI: 10.1002/mma.1490
|View full text |Cite
|
Sign up to set email alerts
|

A semilinear heat equation with a localized nonlinear source and non-continuous initial data

Abstract: Communicated by W. SprößigThis paper is devoted to the study of the Cauchy problem for a semilinear heat equation with nonlinear term presenting a nonlinear source centered in a closed region of the spatial domain . We assume that R n is either a smooth bounded domain or the whole space R n , n 2. The initial data u 0 is assumed to belong to the Lebesgue space L r . /.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Indeed, controlling expression in a such way that it makes sense in L p (Ω) requires more efforts because of the nonlocal and concentrated nonlinear terms. Hence, our existence result cannot be yielded from that one in .…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Indeed, controlling expression in a such way that it makes sense in L p (Ω) requires more efforts because of the nonlocal and concentrated nonlinear terms. Hence, our existence result cannot be yielded from that one in .…”
Section: Introductionmentioning
confidence: 79%
“…By B ( a , b ), we mean the special beta function boldB:(0,)×(0,)(0,) evaluated in the pair ( a , b ), defined by B(a,b)=01(1s)a1sb1ds. Let 1<r,q< and BnormalΩ the open ball of radius trueR˜>0, centered at the origin. The space scriptLr,q, defined in [, page 1912], is the set of all functions φ ∈ L r (Ω) such that φ | ∂ B ∈ L q ( ∂ B ). It is a Banach space endowed with the norm φ=φLr(normalΩ)+φ|BLq(B). In , the authors observed that scriptLr,q has a trace notion on ∂ B so that W 1, r (Ω) is continuously identified with a subset of scriptLr,q and can be isometrically identified with L r (Ω)× L q ( ∂ B ).…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…L r 1 (Ω) × L r 2 (∂Ω)) was employed in [36] and [20] for studying weak solutions for an elliptic and parabolic PDE in bounded domains Ω, respectively. Let us observe that |x ′ | −1 L r 2 (∂R n + ) = ∞ for all 1 ≤ r 2 ≤ ∞ (compare with (1.10)) which prevents the use of the spaces of [20,36] for our purposes.…”
mentioning
confidence: 99%